Роль нарушений обмена азотистых соединений в патогенезе рассеянного склероза = Role of metabolic disorders of nitrogen compounds in the pathogenesis of multiple sclerosis - Naumenko, O. Uy.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2015)
Naumenko O. Uy., Gozhenko A. I. Роль нарушений обмена азотистых соединений в патогенезе рассеянного склероза = Role of metabolic disorders of nitrogen compounds in the pathogenesis of multiple sclerosis. Journal of Education, Health and Sport. 2015;5(10):262-268. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32879 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A262-268 https://pbn.nauka.gov.pl/works/663577 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. РОЛЬ НАРУШЕНИЙ ОБМЕНА АЗОТИСТЫХ СОЕДИНЕНИЙ В ПАТОГЕНЕЗЕ РАССЕЯННОГО СКЛЕРОЗА Role of metabolic disorders of nitrogen compounds In the pathogenesis of multiple sclerosis О. Ю. Науменко, А. И. Гоженко O. Uy. Naumenko, A. I. Gozhenko ГП «Украинский научно-исследовательский институт медицины транспорта» Ukrainian Research Institute for Medicine of Transport Abstract The authors of the survey of 52 patients with different types of MS disease identified a group of neurological disorders, the presence of which does not depend on age and sex of patients, and the severity - brighter for severe types of MS (unsteadiness when walking, blurred vision, fainting, weakness, dysfunction bladder). These disorders are associated with structural-functional state of hypothalamic structures. Defining these patients uric acid in the blood - the status indicator nucleic acid metabolism, showed a decrease in its content in all MS patients, however, the largest decline occurred in patients with the most severe type of MS - primary progressive. The authors suggest that the initial state of nucleic acid metabolism is an important factor in the pathogenesis of MS, since the activity of nucleic acid metabolism determines the possibility of reparative cells and, therefore, their resistance to adverse influences. Key words: multiple sclerosis, uric acid, neurological disorders. Реферат Авторы по результатам обследования 52 больных с разными типами течения рассеянного склероза выделили группу неврологических нарушений, наличие которых не зависит от пола и возраста больных, а выраженность – ярче при тяжелых типах РС (шаткость при ходьбе, нарушение зрения, обмороки, общая слабость, нарушение функции мочевого пузыря). Указанные нарушения связаны со структурно-функциональным состоянием гипоталамических структур. Определение у этих больных содержания мочевой кислоты в крови – показателя состояния нуклеинового обмена, выявило уменьшение ее содержания у всех больных РС, однако наибольшее снижение имело место у больных с самым тяжелым типом течения РС – первично-прогрессирующим. Авторы полагают, что исходное состояние нуклеинового обмена является важным фактором патогенеза РС, так как активность нуклеинового обмена определяет репаративные возможности клеток и, соответственно, их устойчивость к неблагоприятным воздействиям. Ключевые слова: рассеянный склероз, мочевая кислота, неврологические нарушения.